1990
DOI: 10.1302/0301-620x.72b2.2312554
|View full text |Cite
|
Sign up to set email alerts
|

Acetabular cover in congenital dislocation of the hip

Abstract: The exact measurement of femoral head cover is essential for an assessment of reduction of congenital dislocation of the hip. We have compared standard anteroposterior radiographs with computerised tomograms and thereby classified the shape of the acetabular roof into four types. We found that the CE angle of Wiberg is a more reliable measure of head cover when the lateral point of bony condensation of the roof is chosen as the reference point rather than the edge of the bone, where these two points do not ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
147
3
5

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(158 citation statements)
references
References 7 publications
3
147
3
5
Order By: Relevance
“…We found that females with nondypslastic acetabuli were 4°more anteverted than males, similar to findings by Anda et al (3°) [2] and Tallroth and Lepistö (5°) [63]; most other studies did not specify anteversion by sex [4,27,29,30]. Acetabular anteversion for both sexes was no different with dysplastic and nondysplastic acetabuli [3,4,13,29,33,46,48,51,56]. The superior portion of the acetabulum (Torsion 1) was retroverted and the inferior portion (Torsion 2) was anteverted relative to the widest aspect of the acetabulum.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We found that females with nondypslastic acetabuli were 4°more anteverted than males, similar to findings by Anda et al (3°) [2] and Tallroth and Lepistö (5°) [63]; most other studies did not specify anteversion by sex [4,27,29,30]. Acetabular anteversion for both sexes was no different with dysplastic and nondysplastic acetabuli [3,4,13,29,33,46,48,51,56]. The superior portion of the acetabulum (Torsion 1) was retroverted and the inferior portion (Torsion 2) was anteverted relative to the widest aspect of the acetabulum.…”
Section: Discussionsupporting
confidence: 89%
“…Whereas plain radiographs demonstrate superolateral subluxation, axial CT scans make it possible to quantify abnormalities in acetabular orientation and define acetabular defects of the anterior and posterior walls [14,56,72]. Since the mid-1980s, computer software has been available to summarize serial CT scan images, producing twodimensional (2-D) reconstructions and three-dimensional (3-D) surface volumes [42,67,70].…”
Section: Introductionmentioning
confidence: 99%
“…We measured acetabular index (AI) [16] and centre-edge angle (CE-A; measured at the anterior acetabular edge according to the method of Ogata et al) [17,18]. The longest diameter of the capital femoral ossific nucleus on the affected hip was measured, and we evaluated its ratio to that on the unaffected side as a/a 0 (only available in the unilaterally affected children) (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Radiological success results were evaluated according to the Ömeroğlu et al classification (19). Acetabulum evaluation was measured according to criteria reported by Ogata et al (20), and other radiographic measurements [acetabular index (AI), centeredge (CE) angle, head-neck angle, acetabular (Sharp angle etc.)] were obtained according to the original descriptions (21).…”
Section: Methodsmentioning
confidence: 99%